Development and Research of the MZU20D AirSieve Grain Cleaning Machine - P. A. Savinykh; Yu. V. Sychugov; V. A. Kazakov (Сельскохозяйственные машины и технологии)
The authors analyzed the working process and design of the machines involved in grain cleaning. It was revealed that the energy intensity of universal air-sieve machines of domestic and foreign production is 0.86-1.61 kilowatt-hours per ton, the specific metal consumption is 30-700 kilogram-hours per ton.(Research purpose) To develop a high-performance primary-secondary grain cleaning machine with low energy intensity, a high degree of purification of seed and food grain, as well as with the possibility of its installation in continuous grain cleaning and drying lines and complexes.(Materials and methods) The authors created a new structural and technological scheme of the universal grain cleaning machine MZU-20D and its pneumatic system. A prototype was produced with a capacity of 20 tons per hour, with three pneumatic separating channels and three sedimentary chambers of the pneumatic system. They investigated the dust collector of the air system of the MZU-20D machine.(Results and discussion) Using the finite element method, the calculated values and velocity vectors of the air flow at the nodal points of the dust collector cross-section were obtained. The louvered sieve with a porosity of 0.1 was installed at an angle of 30 degrees, in the presence of a dividing partition. The authors optimized the structural and technological parameters according to the three-level Boxing-Bencina matrix plan. Based on the results of the plan’s implementation, rational design parameters of the dust collector were chosen: the depth of the outlet pipe – 0.35 meters, the angle of blinds installation – 30 degrees, the blinds number – 8. It was determined that when the dust collector parameters were brought into line with the above values, the efficiency of the deposition of impurities in it reached 60 percent with hydraulic resistance of 260 pascals. During state tests of the MZU-20D machine at the SPK Rassvet in the Kirov region for cleaning rye grains of the Falenskaya variety, the following characteristics were confirmed: throughput – up to 20 tons per hour, installed capacity – 9 kilowatt, grain purity – at least 98 percent.(Conclusions) It was established that the machine was efficient, performed the technological process qualitatively and could be used, for example, during reconstruction and development of new grain cleaning and drying lines and complexes.